Preparation and photoelectric properties of Si:B nanowires with thermal evaporation method. - Yang Feng; Ping Liang; Ziwen Xia; Weiye Yang; Hongyan Peng; Shihua Zhao (PLoS ONE)
We have successfully prepared a significant number of nanowires from non-toxic silicon sources. Compared to the SiO silicon source used in most other articles, our preparation method is much safer. It provides a simple and harmless new preparation method for the preparation of silicon nanowires. SiNWs (Silicon nanowires), as a novel type of nanomaterial, exhibit many outstanding properties, including the quantum confinement effect, quantum tunneling, Coulomb blocking effect, and exceptional electrical and optical properties. The study of SiNWs is therefore highly significant. In this paper, non-toxic SiO2 powder, Si powder, and B2O3 powder were utilized as raw materials to prepare SiNWs with diameters ranging from 30-60 nm and lengths from several hundred nanometers to tens of microns. The resulting SiNWs have a uniform morphology, smooth surfaces, and are produced in considerable yield. The morphology and structure of the SiNWs were characterized using XRD, SEM, HRTEM, SAED, EDS, and Raman spectroscopy. The results indicate that the prepared SiNWs are pure, uniform, and have a polycrystalline structure. The PL (photoluminescence) spectra show a pronounced UV emission peak at 346 nm, with the optimal excitation wavelength being 234 nm. Measurements with the Keithley 2601B demonstrate that the resistivity of the SiNWs is 4.292 × 108Ω·cm. Further studies reveal that the PL properties of SiNWs are influenced by their size and surface state. These findings have significant implications for understanding the luminescent mechanism of SiNWs and their potential applications in optoelectronics and biomedicine. This paper serves as a reference for the preparation and characterization of SiNWs, highlighting their PL properties and potential use in various applications, including biomedical imaging, sensors, and optoelectronic devices.